OPTIMIZING EMPLOYEE PERFORMANCE: THE ROLE OF KNOWLEDGE MANAGEMENT, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND INNOVATIVE BEHAVIOR - Hafizh Najwan Taqiyyuddin; Noor Arifin (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The tobacco industry, particularly cigarette manufacturing, remains a strategic sector that significantly contributes to the Indonesian economy. In addition to contributing to taxes and excise, this sector also absorbs a large workforce. Within it, employees play a crucial role in maintaining the production process so that it continues to run effectively and efficiently. Therefore, employee performance is a crucial aspect that needs to be continuously improved. In the current era of rapid globalization, this study aims to examine the causal relationships among Knowledge Management (KM), Organizational Citizenship Behavior (OCB), and Innovative Behavior (IB) and employee performance.Methods: This study aims to test hypotheses about the causal relationship between two variables. Data were collected by distributing questionnaires to employees of PR Nunut Urip. The sample size for this study was determined using saturated sampling. Consequently, the sample size for this study was 81 individuals.Results: This study found that knowledge management positively influences employee performance at PR. Nunut Urip. This indicates that employee knowledge is crucial to achieving the company's desired work results. In this study, OCB did not affect to employee performance, as the work culture and environment did not support prosocial and collaborative behavior. The innovative behavior variable had a positive influence on employees. This indicates that employees can apply new ideas to solve existing problems in the field. Keywords: Innovative Behavior, Knowledge, Knowledge Management, Organizational Citizenship Behavior